2007
DOI: 10.1016/j.jconhyd.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Field-scale effective matrix diffusion coefficient for fractured rock: Results from literature survey

Abstract: Matrix diffusion is an important mechanism for solute transport in fractured rock.We recently conducted a literature survey on the effective matrix diffusion coefficient, D i , a key parameter for describing matrix diffusion processes at the field scale. Forty field tracer tests at 15 fractured geologic sites were surveyed and selected for the study, based on data availability and quality. Field-scale D: values were calculated, either directly using data reported in the literature or by reanalyzing the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 110 publications
8
69
0
Order By: Relevance
“…e-mail: qzhou@eticeng.com confirmed by both single-and multi-tracer tests (e.g., Maloszewski et al, 1999). It has been found that the effective matrix diffusion coefficient (D e m ) calibrated using field tracer tests can be orders of magnitude higher than the corresponding matrix diffusion coefficient (D m ) inferred from laboratory experiments on intact rock cores (Hodgkinson and Lever, 1983;Neretnieks, 2002;Andersson et al, 2004;Liu et al, 2004;Zhou et al, 2005). The enhanced matrix diffusion has been attributed to many different mechanisms, such as infilling materials and stagnant water within fractures (Neretnieks, 2002), a degraded and altered matrix zone adjacent to fractures (Hodgkinson and Lever, 1983;Maloszewski and Zuber, 1993;Andersson et al, 2004), and connected small fractures (Wu et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…e-mail: qzhou@eticeng.com confirmed by both single-and multi-tracer tests (e.g., Maloszewski et al, 1999). It has been found that the effective matrix diffusion coefficient (D e m ) calibrated using field tracer tests can be orders of magnitude higher than the corresponding matrix diffusion coefficient (D m ) inferred from laboratory experiments on intact rock cores (Hodgkinson and Lever, 1983;Neretnieks, 2002;Andersson et al, 2004;Liu et al, 2004;Zhou et al, 2005). The enhanced matrix diffusion has been attributed to many different mechanisms, such as infilling materials and stagnant water within fractures (Neretnieks, 2002), a degraded and altered matrix zone adjacent to fractures (Hodgkinson and Lever, 1983;Maloszewski and Zuber, 1993;Andersson et al, 2004), and connected small fractures (Wu et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…It has been proved that the effective hydrodynamic dispersion coefficient in the field is comparatively larger than the hydrodynamic dispersion coefficient in the laboratory [52][53][54][55][56][57][58]. This finding is based on a literature survey of 40 field tracer tests at 15 geologic sites.…”
Section: Hydrodynamic Dispersion Coefficientmentioning
confidence: 99%
“…A number of numerical methods for Laplace transform inversion are available (Cohen, 2007). Among them, the methods of Stehfest (1970) andde Hoog et al (1982) have been extensively employed with semianalytical solutions developed for field pumping and tracer tests (e.g., Moench, 1985;Moridis, 1999;Zhan and Bian, 2006;Zhou et al, 2007). In this research, the de Hoog et al (1982) method was employed for numerical inversion of our analytical solutions.…”
Section: Numerical Inversionmentioning
confidence: 99%